A nexus analysis of tackling disadvantages - Major, Zsuzsa (2021)
The purpose of this qualitative study is twofold. Firstly, it is an attempt to understand the complex social phenomenon of disadvantages, especially in relation to education. Secondly, and most importantly, it is a tool to perpetuate change. The chosen mode of inquiry is nexus analysis, which grounds both the theoretical and methodological choices of this research, complemented with a theoretical background of social inequalities. Guided by the holistic approach of such analysis, I generated data by doing insider ethnography in a marginalised Hungarian setting over the course of three years. The data consists of field work notes and photographs, learning plans and assessments, recorded and transcribed interviews, respectively other types of documentation. The scrutiny follows the steps of a nexus analysis: engaging, navigating, and changing the nexus of practice. The results of this research are interpreted through the changes facilitated by the inductive and participatory mode of inquiry. Namely, by the changes which took place within the nexus of practice of tackling disadvantages as well as the changes within the researcher along the way. However, the aim of the study was to formulate new questions for catalysing further change in the form of social action and inquiry, both addressing the issue of social inequality. In addition, these questions are also formulated.